Etika Profesi dan Profesionalisme Public Relation di Era Digital - Ulfa, Azzahra; Pradana, Farhan; Pane, Haqikah Safni Putri; Zanovsyah, Dhean; Effendi, Erwan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The development of information technology has significantly changed the communication landscape, affecting the practices of Public Relations (PR) in the digital era. This article explores the ethics of the profession and professionalism in the context of PR in the digital era. PR practitioners face new challenges in maintaining integrity, transparency, and honesty in communication in the fast and complex digital world. The research method used is qualitative method with a phenomenological approach. The research results show that Indonesia currently still does not have specific laws related to the internet (Internet Law). Therefore, the Code of Ethics for Public Relations in the digital era is a form of self-imposed regulation and normative in carrying out functions that have the power to influence or engage in social engineering in public opinion simultaneously through cooperation with mass media.